Srimpi Pamor: Wujud Kebudayaan Jawa Dalam Novel Srimpi Pamor Karya Purwadmadi (Kajian Antropologi Sastra) - Az Zahra, Fatimah; Andriyanto, Octo Dendy (Universitas Negeri Surabaya, 2023)
Abstract Srimpi Pamor's novel by Purwadmadi is a Javanese novel that has a story background about Javanese culture, especially the art and culture of the Srimpi dance. The purpose of this research is toexamines the form of Javanese culture in the novel. This study uses research methods qualitative descriptive and using data collection techniques using study techniques bibliography and interviews. The data analysis technique used in this research is technique content analysis. The form of culture in the novel Srimpi Pamor by Purwadmadi in society can be answered through two problem formulations in this study, namely (1) How description of the procedure for selecting Srimpi Pamor dancers in the Srimpi Pamor novel by Purwadmadi? (2) How is the description of the Srimpi Pamor dance in the Srimpi Pamor novel by Purwadmadi? The results of the research show that in the novel Srimpi Pamor by Purwadmadi has a form of culture, especially Javanese art, namely the Srimpi Pamor dance described through the activities of the characters in the novel. The Srimpi Pamor novel studied uses the theory of literary anthropology with clearly illustrates the form of Srimpi Pamor through the procedures for selecting dancers, the order in which the Srimpi Pamor dance is performed from the start to the end, the dress and paes styles used by the dancers. Key Word: Srimpi, Culture, Javanese Abstrak Novel Srimpi Pamor karya Purwadmadi merupakan novel Jawa yang memiliki latar belakang cerita tentang kebudayaan Jawa, khususnya seni budaya tari Srimpi. Tujuan dari penelitian ini adalah untuk mengkaji wujud budaya Jawa dalam novel tersebut. Kajian ini menggunakan metode penelitian deskriptif kualitatif dan menggunakan teknik pengumpulan data dengan menggunakan teknik studi kepustakaan dan wawancara. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik content analysis. Wujud kebudayaan dalam novel Srimpi Pamor karya Purwadmadi di masyarakat dapat dijawab melalui dua rumusan masalah dalam penelitian ini, yaitu (1) Bagaimana gambaran tata laksana pemilihan penari Srimpi Pamor dalam Novel Srimpi Pamor oleh Purwadmadi? (2) Bagaimana gambaran tari Srimpi Pamor dalam novel Srimpi Pamor karya Purwadmadi? Hasil penelitian menunjukkan bahwa dalam novel Srimpi Pamor karya Purwadmadi terdapat salah satu wujud kebudayaan khususnya kesenian Jawa yaitu tari Srimpi Pamor yang digambarkan melalui aktivitas tokoh-tokoh dalam novel tersebut. Novel Srimpi Pamor yang dikaji meggunakan teori antropologi sastra dengan jelas menggambarkan wujud Srimpi Pamor melalui tata cara pemilihan penari, urutan pementasan tari Srimpi Pamor dari awal hingga akhir, hingga tata busana dan tata paes yang digunakan oleh para penari. Kata Kunci: Srimpi, Kebudayaan, Jawa